Avaliaç\~ao de impacto do Prouni sobre a perfomance acadêmica dos estudantes - Kalinca Léia Becker; Mário Jorge Cardoso de Mendonça (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– This study aims to analyze the quantile treatment effect of Prouni on the students' Enade grades from 2015 to 2017. The results indicated that the impact of the program was positive throughout the grades distribution, mainly for students who received full scholarship. The impact was also greater for students who declare family income of more than three minimum wages, which reinforces the argument that it is necessary to focus the policy resources on low-income students and prioritize those with the highest budget constraints. The effect of the program was also positive for students enrolled in institutions with quality concept 4 and 5. Thus, the study results confirm that financial aid policies for low-income students are able to combine inclusion and quality in higher education.
Keywords: D22; H52; I21; 330; educational credit; Prouni; quantilic regression; academic performance